Gender inequalities in immunization of children in a rural population of Barabanki, Uttar Pradesh - Ahuja, Ravindra; Rajpurohit, Ambresh Chand; Ahuja, Rajat (Indian Journal of Community Health, 2014)
Background: There is evidence of inequalities in immunization in India, despite the fact that childhood immunization has been an important part of maternal and child health services since the 1940s [1]. Objective: To evaluate the gender inequality in the missed opportunity for immunization in pre-school children in the rural population of Barabanki, Uttar Pradesh, India. Methods: This was a cross-sectional study conducted in the rural areas of Barabanki district among the children of 1- 2 years of age. The information was collected on pre-designed questionnaire. A total of 15 villages were covered. A door to door survey was conducted in all the villages. There was 6% non-response due unavailability of mother/father of children. A total of 447 children were included in the study. Results: Out of the total children, 50.6% (226/447) were males and 49.4% (221/447) were females. Overall, 49.7% were fully immunized and 20.4% partially immunized. However, 5.8% were having contraindication for immunization. The percentage of fully immunized children was higher among males (54.4%) compared with females (44.8%). However, the percentage of partially immunized was found to be higher among females (21.3%) than males (19.5%). The percentage of contraindication was similar among both male and female children. Conclusion: Missed opportunity for immunization can be brought down by creating awareness periodically once in 2 or 3 months for immunization among health personnel.